Probing lipid-protein adduction with alkynyl surrogates: application to Smith-Lemli-Opitz syndrome[S] - Katherine Windsor (Journal of Lipid Research, 2013)
Lipid modifications aid in regulating (and misregulating) protein function and localization. However, efficient methods to screen for a lipid's ability to modify proteins are not readily available. We present a strategy to identify protein-reactive lipids and apply it to a neurodevelopmental disorder, Smith-Lemli-Opitz syndrome (SLOS). Alkynyl surrogates were synthesized for polyunsaturated fatty acids, phospholipids, cholesterol, 7-dehydrocholesterol (7-DHC), and a 7-DHC-derived oxysterol. To probe for protein-reactive lipids, we used click chemistry to biotinylate the alkynyl tag and detected the lipid-adducted proteins with streptavidin Western blotting. In Neuro2a cells, the trend in amount of protein adduction followed known rates of lipid peroxidation (7-DHC >> arachidonic acid > linoleic acid >> cholesterol), with alkynyl-7-DHC producing the most adduction among alkynyl lipids. 7-DHC reductase-deficient cells, which cannot properly metabolize 7-DHC, exhibited significantly more alkynyl-7-DHC-protein adduction than control cells. Model studies demonstrated that a 7-DHC peroxidation product covalently modifies proteins. We hypothesize that 7-DHC generates electrophiles that can modify the proteome, contributing to SLOS's complex pathology. These probes and methods would allow for analysis of lipid-modified proteomes in SLOS and other disorders exhibiting 7-DHC accumulation. More broadly, the alkynyl lipid library would facilitate exploration of lipid peroxidation's role in specific biological processes in numerous diseases.